Translating magnetic resonance imaging research in clinical practice for dementia: The Oxford Brain Health Centre. (1st February 2022) - Griffanti, Ludovica; Clare O'Donoghue, M.; Blane, Jasmine; Mitchell, Robert; Aikin, Nicola; Lindsay, Karen; Campbell, Jon; Semple, Juliet; Nobis, Lisa; Raymont, Vanessa; Martos, Lola; Mackay, Clare
Abstract: Background: The Oxford Brain Health Centre (BHC) is a pioneering psychiatry‐led joint clinical‐research service launched in 2020. It provides NHS patients with existing memory problems access to high‐quality assessments not routinely available in clinical practice, including MRI rather than CT. This abstract describes the MRI protocol of the BHC, designed to translate dementia research advances into clinical practice, and shows preliminary data from the BHC pilot. Method: The BHC MRI protocol (details in Table 1) is structured to include core clinical sequences (high‐resolution T1, FLAIR, SWI and 3D DWI) and optional research sequences (TOF, ASL, DWI, resting state fMRI). Patients can consent to use of clinical scans for research, additional research sequences, and recontact about future research. Sequences were matched as much as possible to the UK Biobank (UKB) imaging protocol (Miller et al., 2016 Nat Neurosci.) to take advantage of its high‐quality data, clinically feasible acquisition time, and availability of big population data. Additional scans on healthy controls are planned to improve generalizability of UKB and enrich the age range of interest. Result: Thirty‐three patients attended the BHC between August and December 2020 (average age 77.5 years, age range 66‐90 years, 58% female). 94% of patients completed the clinical scans and consented use for research, 64% consented to additional research sequences and 42% completed the research scan. Table 1 details the number of currently available scans for each modality. An adapted version of the UK Biobank pipeline (Alfaro‐Almagro et al., 2018 Neuroimage) is being developed to extract quantitative measures from the scans (imaging derived phenotypes, IDPs). For example, Figure 1 shows how hippocampal volumes for 11 BHC patients compare with UKB data: most of them fall in the lower percentiles, suggesting potentially pathological deviations from the norm. Conclusion: The data acquired in the first months of the BHC pilot phase demonstrate that the MRI protocol is well tolerated and provides good quality data both for research and clinical purposes. Future work aims to integrate quantitative measures in the radiology reports of the BHC and evaluate their impact in the clinical practice.